Families, Mental Health, and Delinquency: Testing Sexual Crime Typologies of Youth Who Sexually Harm - Brown, Adam (Youth violence and juvenile justice, 2022)
Researchers have made great strides in identifying risk factors associated with the commission of sexual harm by youth. However, many of the risk factors associated with youth who sexually harm (YSH) are also associated with nonsexual delinquency, making it hard to create typologies of YSH to target prevention and treatment. To eliminate an overlap with nonsexually offending general delinquents, Brown (2019) used latent class analysis to identify four unique classes of youth based only on their sexual crime characteristics. A research implication of Brown's findings was to explore the relationship of the classes to characteristics associated with sexual crime by youth to identify targeted treatment implications and opportunities to prevent sexual crime. In this study, the authors used chi-square analyses and logistic regression to test the relationships of mental health, family factors, concurrent delinquency with the classes identified in Brown's (2019) study using the same sample (N = 573) used by Brown. Findings highlight the potential differing etiology and treatment needs of YSH according to their offense characteristics. Treatment implications and directions for future research are offered.